2019
DOI: 10.1111/ijlh.13143
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of a delta check model in haematology automated counting improves data validation

Abstract: IntroductionThe delta check quality control measure has been applied in haematology testing for a long time. Although the delta check graph of haematology test had been reported by Berend Houwen in 1989, problems still exist in its clinical application. This study aims to provide a simplified and practical process for the improvement of validity in haematology testing.MethodsWe analysed a total of 5260 patients with two sequential complete blood counting results, taken in 1 week, to verify the delta check curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Delta checks, at least indirectly, have been included in accreditation requirements issued by the Joint Commission International, International Organization of Standardization, and CAP, highlighting the significance of delta checks and its application as a part of good laboratory practice. Moreover, the re‐inspection rate during clinical validation of results in an experimental study was reduced by 7.01%, 4.66%, and 7.86% in the oncology, hematology, and other departments, respectively, reflecting improved working efficiency through delta checks 10 …”
Section: Figurementioning
confidence: 99%
“…Delta checks, at least indirectly, have been included in accreditation requirements issued by the Joint Commission International, International Organization of Standardization, and CAP, highlighting the significance of delta checks and its application as a part of good laboratory practice. Moreover, the re‐inspection rate during clinical validation of results in an experimental study was reduced by 7.01%, 4.66%, and 7.86% in the oncology, hematology, and other departments, respectively, reflecting improved working efficiency through delta checks 10 …”
Section: Figurementioning
confidence: 99%
“…Some recent studies have used machine learning for delta check [14,15]; however, few studies on hematologic tests have been published. Fu, et al [16] simplified the delta check limitation formulae for data review and reported a new delta check model for automated complete blood counting that improved data validation. Miller, et al [17] suggested a new mean corpuscular volume (MCV)-based delta check method and limits ( > 3.0 fL) for hematology laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Fu, et al . [ 16 ] simplified the delta check limitation formulae for data review and reported a new delta check model for automated complete blood counting that improved data validation. Miller, et al .…”
Section: Introductionmentioning
confidence: 99%